1989
DOI: 10.3366/anh.1989.16.2.191
|View full text |Cite
|
Sign up to set email alerts
|

Origin and usage of the geological terms orsten, stinkstone, and anthraconite

Abstract: Orsten, stinkstone, and anthraconite are synonymous terms in theory but not in practice. In order to trace their development, usage by European geologists through more than 200 years has been investigated. The original definitions and references are examined and found to deviate essentially from the ones in modern geological literature. Another set of poorly defined terms, bitumen and carbon, are found to play a major role in the confusion. A revision of commonly used terms rather than uncritical reproduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…32 V. Berg-Madsen discussed the problem of terminology in relation to the dark bituminous limestones of Scandinavia which have been given synonymous names including stinkstone, anthraconite and orsten. 33 While orsten is still used for these limestones in northern Europe, she showed that modern interpretations of the terms deviate markedly from the original meaning. Throughout early texts terms are used which may not be known to latter-day geologists or historians of geology, or else terms are used today which are at variance with past usage.…”
Section: Case Study 2 : Robert Jameson and Understanding Early Geologmentioning
confidence: 98%
“…32 V. Berg-Madsen discussed the problem of terminology in relation to the dark bituminous limestones of Scandinavia which have been given synonymous names including stinkstone, anthraconite and orsten. 33 While orsten is still used for these limestones in northern Europe, she showed that modern interpretations of the terms deviate markedly from the original meaning. Throughout early texts terms are used which may not be known to latter-day geologists or historians of geology, or else terms are used today which are at variance with past usage.…”
Section: Case Study 2 : Robert Jameson and Understanding Early Geologmentioning
confidence: 98%
“…List of terms used in online search for glendonites Anthraconite (Anthrakonit, антраконит). This term is also frequently using for any black limestone bands or concretions (see Berg-Madsen, 1989 for review), but in some cases (i.e. Early Paleozoic of Estonia and Saint-Petersburg area) this term was applied solely for glendonites for ~ 150 years (Hausmann, 1806: introduction of the term 'Anthraconite' for black 5 limestones; Karpinsky, 1887: first usage of this term for Ordovician glendonites)…”
Section: Supplementarymentioning
confidence: 99%
“…The latter name derives from the fact that the rock is so enriched in hydrocarbons that if it is cracked open with a hammer there is often a pungent stench of kerosene or crude oil. The name 'Orsten' (a Swedish name for stinkstone) is derived from an old veterinary term, as the limestone was processed and used for curing diseases in pigs and other domestic animals (Bromell, 1729;Regnéll, 1949;Berg-Madsen, 1989). Regardless of the unflattering name, strange odor and dull color, these limestones can contain magnificently preserved microscopic fossils, known as the 'Orsten' fossils.…”
Section: The Alum Shale Formationmentioning
confidence: 99%